How large are the differences between originator and generic prices? Analysis of five molecules in 16 European countries - Vogler, Sabine (Farmeconomia. Health Economics and Therapeutic Pathways, 2012)
OBJECTIVE: To survey the price differences between originators and generics for a selected basket of molecules and to analyze similarities and differences with regard to the countries included and their generic policies. METHODS: Ex-factory prices as of November 2011 of five molecules provided from the Pharma Price Information (PPI) service of the Austrian Health Institute were analyzed for 16 European countries (Austria, Belgium, Denmark, Finland, France, Germany, Greece, Ireland, Italy, the Netherlands, Norway, Portugal, Spain, Switzerland, Sweden, UK). The selected molecules were gemcitabine, mycophenolate mofetil, olanzapine, risperidone and sumatriptan. For a specific presentation (same pack size, dosage and pharmaceutical form) of each molecule, the prices of the original product and the “most common generic” as defined by PPI were compared. RESULTS: Considerable variations among the extent of price differences between originator and generic were identified (gemicitabine: lowest price difference of 1.4% between originator and generic in Belgium and highest difference of 73.4% in Portugal; mycophenolate mofetil: 3.4% Norway – 71.7% Netherlands; olanzapine: 0.1% Spain – 97.1% Sweden; risperidone: 0.9% Netherlands – 97.3% UK; sumatriptan: 5.8% Greece – 95.0% Denmark). Further, no difference at all between originator and generic prices was found for some molecules in a few countries (Norway: for 4 of the 5 molecules analyzed; Spain: 3; Belgium: 2; in Austria, France and Greece for one molecule respectively). For the five molecules of the sample, Greece, Spain, Ireland and Norway consistently displayed lower price differences whereas Denmark, Finland and Sweden tended to show higher differences between originator and generic prices. CONCLUSION: Even if this research is illustrative and not representative due to the small sample size, results suggest confirming large differences across Europe. It appears that countries (e.g. Denmark, Sweden) with strong generic policies, particularly based on competition and involving elements of enforcement, tend to have higher differences between originator and generic prices. Further research, notably with a broader basket, is recommended.